Relationship Between Coronary Flow Reserve and Glycated Hemoglobin in Patients With Diabetes Mellitus Using Radionuclide Myocardial Perfusion Imagin - Faheem, Muhammad; seher, Saima; Khan, Muhammad Nadir; Nisa, Kiran; Khan, Ateeq ur Rehman; mehreen, Sobia (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the relationship between coronary flow reserve (CFR) and glycosylated hemoglobin (HbA1c) in patients with type 2 diabetes mellitus using radionuclide myocardial perfusion imaging (MPI).Study Design: Analytical Cross-Sectional Study.Place and Duration of Study: Armed Forces Institute of Cardiology (AFIC), Rawalpindi, Pakistan, from Jun to Dec 2025.Methodology: Ninety-eight adults (18–70 years), irrespective of gender, with type 2 diabetes mellitus referred for myocardial perfusion imaging were screened. Consecutive sampling was used to enroll all eligible patients who met the inclusion criteria during the study period. Patients with obstructive substantial valvular disease, left ventricular ejection fraction less than 50%, and coronary artery disease, arrhythmias, or advanced renal impairment were excluded. All participants underwent standardized SPECT myocardial perfusion imaging with pharmacological stress were indicated to all patients. Coronary flow reserve was calculated from stress-to-rest myocardial tracer uptake. Glycemic control was assessed by HbA1c using a Roche analyzer.Results: There were ninety-eight patients; 45 (45.9%) had adequate glycemic control (HbA1c